STUDY OF IN SITU CYANIDE DETOXIFICATION ON GOLD PROCESSING TAILING AT PONGKOR GOLD MINE - Lili Tahli; Tatang Wahyudi (Indonesian Mining Journal, 2008)
Currently, gold processing unit at Pongkor mine processes cyanide-containing waste at the end pipe or known as final process. Due to the increase of environmental awareness from the community, such a process needs to be re-evaluated. This relates to tight regulation regarding safe waste prior to releasing to the nature. Conflicts will arouse when population at surrounding area increases fast. To anticipate such conflicts, the gold processing unit of Pongkor mine proposes a scenario dealing with waste processing improvement from the end pipe process to the whole one. It includes reagent use optimization and waste minimization including its recycle. In situ cyanide detoxification is one of waste minimization processes conducted at Pongkor mine. In terms of comparing which one of the methods is the best in reducing cyanide within wastes, a series of cyanide reduction tests employed Inco’s and Degussa methods at a laboratory scale. To reduce high cyanide concentration of the wastes, the used reagents in Inco’s method include Na2 S2O5, CuSO4.5H2O and pressured by the air while Degussa method applied H2O2 and CuSO4.5H2O. The results from this experiment suggest that Inco’s technology is able to detoxify cyanidation effluents better than that of Degussa technology.